Training load influences gut microbiome of highly trained rowing athletes - Charlesson, B.; Jones, J.; Abbiss, C.; Peeling, P.; Watts, S.; Christophersen, C. T. (Journal of the International Society of Sports Nutrition, 2025)
Background: Despite the importance of the gut microbiome on physical performance and health, little is known on the impact of training on an athlete`s gut health.